2018
DOI: 10.17392/954-18
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of the clinical sign of limited hip abduction for developmental dysplasia of the hip (DDH)

Abstract: <p><strong>Aim<br /></strong> To assess the relationship between the clinical sign of limited hip abduction and developmental dysplasia of the hip (DDH). <strong>Methods<br /></strong> A research was conducted on 450 newborns at the Neonatal Unit at the Clinic of Gynaecology and Obstetrics and the Orthopaedics and Traumatology Clinic of the University Clinical Centre, Tuzla, between 30 th August 2011 and 30 th Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In this review, we compiled many studies, allowing us to determine which countries screen universally (Austria [1,[23][24][25], Bosnia and Herzegovina [26], Poland [47], Slovenia [14,48], the Czech Republic [27,28,64], and Germany [34][35][36][37]) and selectively (the United Kingdom [21,[52][53][54][55][56][57], Italy [29,43,44], Denmark [30][31][32], Spain [49,50], the Netherlands [11,45], Hungary [40], Norway [19,46], France [18,33], Ireland [17,41,42], Greece [38], Sweden [20], and Ukraine [51]). Summarised information on DDH screening approaches can be found in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we compiled many studies, allowing us to determine which countries screen universally (Austria [1,[23][24][25], Bosnia and Herzegovina [26], Poland [47], Slovenia [14,48], the Czech Republic [27,28,64], and Germany [34][35][36][37]) and selectively (the United Kingdom [21,[52][53][54][55][56][57], Italy [29,43,44], Denmark [30][31][32], Spain [49,50], the Netherlands [11,45], Hungary [40], Norway [19,46], France [18,33], Ireland [17,41,42], Greece [38], Sweden [20], and Ukraine [51]). Summarised information on DDH screening approaches can be found in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Screening approach in the Czech Republic is presented in Figure 3. Bosnia and Herzegovina does not currently have an established screening pro gramme [26]; however, the authors of the study conducted a universal physical and ultra sound examination of the hip on the day of birth. All were performed by an orthopaedi surgeon using Graf's ultrasound method.…”
Section: Czech Republicmentioning
confidence: 99%
“…Laborie et al conducted a randomized trial regarding the use of universal ultrasound; ultrasound use increased the early diagnosis of DDH to a nonstatistically significant level; however, in the long-term this was not clinically significant as it did not influence the frequency of chronic complications of the disease [17]. A study by Čustović et al also appears to be in favor of a simple clinical examination; it was shown that unilateral limited hip abduction could a valuable clinical sign of DDH (positive predictive value = 40.3% and negative predictive value = 80.4%), which could be used for diagnostic purposes [18] There has been, however, contradictory evidence regarding the effectiveness of DDH screening with a simple clinical examination, as many cases of DDH still remain undiagnosed when using this approach [7]. Reidy et al investigated the screening effectiveness of the hip examination at 6-8 weeks, performed by a general practitioner, and found that the sensitivity of examination was only 19.4%, as well as that four of five children with DDH remained undiagnosed [19].…”
Section: Ddh Screeningmentioning
confidence: 97%